1986
DOI: 10.1152/jappl.1986.61.2.500
|View full text |Cite
|
Sign up to set email alerts
|

Control of ventilation in extreme-altitude climbers

Abstract: Ten climbers who participated in the Nepal-Japan Kangchenjunga Expedition (altitude, 8,478-8,586 m) in 1984 were examined for their hypercapnic and isocapnic hypoxic ventilatory responses (HCVR and HVR) at sea level before and after the expedition. Five climbers who reached an altitude higher than 8,000 m, [designated high-performance climbers (HPC)] exhibited significantly higher HVR than five climbers who did not [low-performance climbers (LPC)]. On the other hand, no significant difference in HCVR was seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 0 publications
2
27
1
Order By: Relevance
“…Everest by SCHOENE et al (1984) and for Mt. Kangchenjunga by MASUYAMA et al (1986). Though this study did not find any relationship between daytime climbing performance and HVR (all climbers reached the summit), the exercise test done at 5,360 m in this expedition revealed that the higher HVR a climber had, the less desaturation during exercise (HASAKO et al, 1988), which agreed with the result of SCHOENE et al (1984).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Everest by SCHOENE et al (1984) and for Mt. Kangchenjunga by MASUYAMA et al (1986). Though this study did not find any relationship between daytime climbing performance and HVR (all climbers reached the summit), the exercise test done at 5,360 m in this expedition revealed that the higher HVR a climber had, the less desaturation during exercise (HASAKO et al, 1988), which agreed with the result of SCHOENE et al (1984).…”
Section: Discussionsupporting
confidence: 72%
“…HCVR was also evaluated as 4 'i/4 P02 and 4P02/4P02. Methodological details have been described elsewhere (MASUYAMA et al, 1986). Sleep studies by polysomnography were also done in eight climbers.…”
Section: Methodsmentioning
confidence: 99%
“…This intersubject variability is explained, at least in part, by genetic factors [16][17][18] and remains unchanged for many years in healthy subjects [19]. Low HVR values have been shown to be associated with poor exercise capacity at high altitude [6,7], severe nocturnal desaturation in sleep apnoea syndrome [8], hypercapnic respiratory failure in COPD [9][10][11], and possibly even fatal asthma attacks [12]. Since these conditions are all associated with exercise or hypercapnia, the strong influence on the pathophysiology of hypoxic chemosensitivity may be a consequence of enhancement of hypoxic chemosensitivity itself and also amplification of intersubject variability under such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that hypoxic chemosensitivity evaluated by HVR has a wide interindividual variability [4,5], and that the variability in hypoxic chemosensitivity is a factor accounting for intersubject variation in pathophysiological responses under a variety of hypoxic conditions. For instance, a lower HVR is shown to be associated with poorer performance at high altitude [6,7], more severe nocturnal desaturation in sleep apnoea syndrome [8], hypercapnic respiratory failure in chronic obstructive pulmonary disease (COPD) [9][10][11], and even near-death cases of bronchial asthma [12]. It is, thus, clinically important to examine the interaction of HVR with exercise and/or hypercapnia.…”
mentioning
confidence: 99%
“…Many reports have suggested that several months are needed for hypoxic deacclimation, particulary in the pulmonary function of rats (see references cited by FRIED and REID, 1984) and also in man (FoRSTER et al, 1971;MASUYAMA et al, 1986), with earlier recovery in the hematological changes. For cardiovascular function, on the other hand, such long-term studies are lacking, though some parameters in man seem to recover within several days after descent from highaltitude stay (VOGEL et al, 1967;BALASUBRAMANIAN et al, 1978), and rats with cardiac hypertrophy induced by intermittent exposure to simulated high altitude showed the regression with a half-time of about 7 days (SIZEMORE et al, 1973).…”
mentioning
confidence: 99%